Zentrenausrichtung im Raum Tokyo: Charakteristika und Probleme aus zentralörtlicher und raumplanerischer Sicht - Flüchter, Winfried (ERDKUNDE, 1980)
This study is concerned with the exposition of principles of important and typically Japanese orientations of the suburban and Umland population of Tokyo as to central places. While taking into account the fact of employment in the city, the power of attraction of diverse urban foci to the people of the region of the capital is interpreted here especially from the point of view of spatial ordering. The introduction (Chapter I) is followed by a description of the centres and their characteristics in the Tokyo Region (Chapter TI). The main investigation (Chapter III), after providing a rough orientation for the inner city central place preference (III.l), is divided into case studies of the topics: shopping (III.2), subdivided according to goods of daily, periodic and episodic requirement and going out/ pleasure (III.3),especially from the commuter’s point of view; it also includes the question of the citizens’ consciousness of identity with their city (III.4). The second main part, is a summary and spatially orienting analysis (Chapter IV), treats the following themes: (1) problems of inner city processes of concentration by way of frequent identity of work trips with social trips and shopping trips, and the accordingly correlated community of location of office-, shopping and pleasure centres; (2) and (3) continuity of the attractiveness of inner city centres (main centres and ring centres) in spite of a starting increase in the attractiveness of sub-centres in the suburban and Umland zones; (4) considerable centrifugal extension of the network of the gravitational centres into the Umland with short-lived though considerable instabilities in the hierarchy of centres as well as the alignment of centres; (5) competition between large and small retail trade as a social and micro-locational problem; (6) significance of daily shopping trips for the local and neighbourhood centres; (7) position of importance of an effective means of transport by rail for the visitors to the centres and for the continuing power of the urban centres’ radiation,which, being lively foci of city life, humming with people, do not have to fear competition by large drive-in shopping centres